Slow versus fast rewarming after hypothermic circulatory arrest: effects on neuroinflammation and cerebral oedema. (14th May 2020) - Linardi, Daniele; Walpoth, Beat; Mani, Romel; Murari, Angela; Tessari, Maddalena; Hoxha, Stiljan; Anderloni, Marco; Decimo, Ilaria; Dolci, Sissi; Nicolato, Elena; Bontempi, Pietro; Merigo, Flavia; et al.
Abstract: OBJECTIVES: Among the factors that could determine neurological outcome after hypothermic circulatory arrest (HCA) rewarming is rarely considered. The optimal rewarming rate is still unknown. The goal of this study was to investigate the effects of 2 different protocols for rewarming after HCA on neurological outcome in an experimental animal model. METHODS: Forty-four Sprague Dawley rats were cooled to 19 ± 1°C body core temperature by cardiopulmonary bypass (CPB). HCA was maintained for 60 min. Animals were randomized to receive slow (90 min) or fast (45 min) assisted rewarming with CPB to a target temperature of 35°C. After a total of 90 min of reperfusion in both groups, brain samples were collected and analysed immunohistochemically and with immunofluorescence. In 10 rats, magnetic resonance imaging was performed after 2 and after 24 h to investigate cerebral perfusion and cerebral oedema. RESULTS: Interleukin 6, chemokine (C-C motif) ligand 5, intercellular adhesion molecule 1 and tumour necrosis factor α in the hippocampus are significantly less expressed in the slow rewarming group, and microglia cells are significantly less activated in the slow rewarming group. Magnetic resonance imaging analysis demonstrated better cerebral perfusion and less water content in brains that underwent slow rewarming at 2 and 24 h. CONCLUSIONS: Slow rewarming after HCA might be superior to fast rewarming in neurological outcome. The present experimental study demonstrated reduction in the inflammatory response, reduction of inflammatory cell activation in the brain, enhancement of cerebral blood flow and reduction of cerebral oedema when slow rewarming was applied.